Gamification elements and engagement: exploring students’ perception in an English reading course - Ramos, Samantha (2023)
Gamification has been widely employed as a pedagogical tool for fostering interaction and learning in class, including in foreign language teaching contexts. The gamification process may modify the structure or the content of a course with the use of specific strategies, such as the attribution of points and acknowledgements, ranking systems, storytelling, and others. Still, there is a lack of formal methodological procedures on how to design such strategies, as well as how they affect the engagement of students. As an attempt to expand the studies on the use of gamification as a pedagogical tool, this research aims at identifying which elements are likely to promote or limit engagement opportunities in class according to the student’s perception. Data was generated through a questionnaire, which was applied on a remote instrumental reading course, and components of quantitative and qualitative research were used to analyze responses to open-ended and Likert-scale questions. The results indicate positive and challenging aspects of certain gamification elements. High importance was attributed to elements that provided task guidance and content feedback, fostered decision-making opportunities towards content, and created moments for interaction with the environment and peers. Elements that appeared to limit engagement were related to individual collaboration in group work, content complexity regarding the target language, introduction of new digital tools and systems, and personal topics of interest; accordingly, these items require careful implementation.